2016
DOI: 10.1007/s12640-016-9688-3
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of l-Arginine:NO:cGMP Pathway in Tolerance to Flunitrazepam in Mice

Abstract: The goal of the study was to investigate the effects of drugs modifying l-arginine:NO:cGMP pathway on the development of tolerance to flunitrazepam (FNZ)-induced motor impairment in mice. FNZ-induced motor incoordination was assessed on the 1st and 8th days of experiment, using the rotarod and chimney tests. It was found that (a) both a non-selective nitric oxide synthase (NOS) inhibitor: N G-nitro-l-arginine methyl ester (l-NAME) and an unselective neuronal NOS inhibitor: 7-nitroindazole (7-NI) inhibited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…We can assume that in the paradigm applied in our experiment the L‐arginine‐NO‐cGMP‐dependent pathway plays an important role in the expression of sensitization to mephedrone‐induced responses. In our previous studies, we demonstrated that the tested substances affecting the L‐arginine‐NO‐cGMP‐dependent pathway do not influence the spontaneous locomotor activity of male albino Swiss mice when given alone at the doses used in the current experiment 59–62 . Therefore, the observed effects could not have been noted because of disturbed locomotor activity of mice exerted by the tested agents.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…We can assume that in the paradigm applied in our experiment the L‐arginine‐NO‐cGMP‐dependent pathway plays an important role in the expression of sensitization to mephedrone‐induced responses. In our previous studies, we demonstrated that the tested substances affecting the L‐arginine‐NO‐cGMP‐dependent pathway do not influence the spontaneous locomotor activity of male albino Swiss mice when given alone at the doses used in the current experiment 59–62 . Therefore, the observed effects could not have been noted because of disturbed locomotor activity of mice exerted by the tested agents.…”
Section: Discussionmentioning
confidence: 66%
“…In our previous studies, we demonstrated that the tested substances affecting the L-arginine-NO-cGMP-dependent pathway do not influence the spontaneous locomotor activity of male albino Swiss mice when given alone at the doses used in the current experiment. [59][60][61][62] Therefore, the observed effects could not have been noted because of disturbed locomotor activity of mice exerted by the tested agents. Similarly to the outcomes of our study, 7-nitroindazole blocked the expression of psychomotor sensitization produced by methamphetamine, 36 3,4-methylenedioxymethamphetamine, 33 methylphenidate 37 and cocaine, 38 whereas L-NAME inhibited the expression of sensitization produced by amphetamine 35 and morphine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NO is an important messenger molecule in the brain since it takes part in the regulation of neuronal excitability, synaptic plasticity, learning, emotions, seizure activity, drug tolerance, and many other brain processes [30,31]. Previously, our research team demonstrated that this NO-dependent signalling is implicated in the development of tolerance to diazepam [32] and flunitrazepam [33], whereas Mansouri et al [34] and Ozdemir et al [35], confirmed its role in morphine tolerance. NO is synthesized from L-arginine by NO synthase (NOS).…”
Section: Introductionmentioning
confidence: 81%